Optimisation de la fermentation en milieu semi-solide pour la production d’ablo, pain cuit a la vapeur d’Afrique de l’ouest - Agro, A.; Akissoé, N.H.; Manful, J.; Mestres, C.; Hounhouigan, Djidjoho J. (African Journals Online, 2014)
Objective: To test three equipments for the fermentation of rice semi-solid dough to produce ablo (a steamy and foamy bread) and then, to investigate the effect of fermentation temperature and duration and the rate of yeast on some critical parameters Methodology and results: The semi-solid dough was fermented for four hours in glass box, icebox and aluminum bowls (Control) at ambient temperature (26-27 °C). In addition, the effect of fermentation temperature and duration and the rate of yeast were investigated using full factorial design, with values ranging between 2 and 6 hours, 22 and 30 °C and 1 and 3 g/Kg flour. The pH, titrable acidity, the dry matter content and the quantity of moss/foam were determined as well as the yeast and fungi counts. Except for the moss produced and the dry matter content, no significant effect was evidenced on all other parameters measured as far as the equipment is considered. Significant and positive effects of temperature, duration and the rate of yeast (P<0.05) were observed on the quantity of moss produced Conclusion and application: The glass box, followed by icebox were the best fermenting equipments of the dough, giving great amount of moss produced, probably due the airtight or the regular form of both equipments. At the dough yield of 180, the optimal values of these factors for upgrading fermentation of the rice dough included 30 °C, 3 g of yeast per Kg of flour and 4 hours of resting. These conditions was validated and lead to the fermented dough with pH ranging between 4.42 and 4.64, dry matter between 29.99 et 38.79% and moss height varying from 4.85 to 5.62 cm. In further work, it will be appreciated to test these optima conditions on maize or the mix rice-maize flour since they are raw materials for ablo production.